1984
DOI: 10.3109/03091908409032067
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between arterial pulse-wave velocity and pulse frequency at different pressures

Abstract: Pulse-wave velocity was measured in isolated canine common carotid arteries using sinusoidal frequency pulses of 1, 2, 5, 10, 15 and 20 Hz at 50, 100 and 150 mmHg. It was found that the pulse-wave velocity was independent of frequency and dependent on pressure. Using the Moens-Korteweg equation, the predicted pulse-wave velocity (y) was compared with measured pulse-wave velocity (x). A good correspondence was found (y = 1.063 x - 0.337, with a correlation coefficient of 0.963). The propagation velocity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 7 publications
1
34
2
Order By: Relevance
“…Despite earlier in vivo pacing experiments suggesting an effect on PWV (24,26), other studies showed no relationship (1), and no effect of heart rate was observed under controlled conditions in vitro (8). The time course of the steadily slowing heart rate clearly did not correspond to the more complex pattern of changes in PWV observed in this study.…”
Section: Do the Observed Postexercise Changes In Pwv Reflect Changes contrasting
confidence: 47%
“…Despite earlier in vivo pacing experiments suggesting an effect on PWV (24,26), other studies showed no relationship (1), and no effect of heart rate was observed under controlled conditions in vitro (8). The time course of the steadily slowing heart rate clearly did not correspond to the more complex pattern of changes in PWV observed in this study.…”
Section: Do the Observed Postexercise Changes In Pwv Reflect Changes contrasting
confidence: 47%
“…The accuracy of derived BP values was low in comparison with the conventional method. 29 In this study, BP was estimated based on PTT by the linear function but a number of authors obtained a nonlinear relationship between PTT and BP, [16][17][18] while others reported linear relations which was in consistent with our study. 20,22 In the present study, SBP was used to monitor BP based on PTT, because several studies have shown that SBP could be measured more accurately than diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 79%
“…13 Pulse transition time (PTT) is another method, acting based on continuous recording of ECG and pulse wave. The main features of PTT method including safety, noninvasive and continuous BP monitoring has been documented in a vast array of studies, [14][15][16][17][18] but ECG recording impose another set of the complexity to hemodialysis. This study aimed to develop a system for continuous monitoring of BP in patients undergoing hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…sympathetic nervous activity, circulating hormones) 31 and regional (e.g. endothelium-derived vasoactive substances, exercise muscle-derived metabolites), 32 HR (>120 bpm) 33 or simply by a more distended artery because of increased mean arterial pressure, 34 these SCI-specific conditions may cause variation in PWV.…”
Section: Discussionmentioning
confidence: 99%